2022
DOI: 10.3390/jcm11020341
|View full text |Cite
|
Sign up to set email alerts
|

CDCP1 Expression Is a Potential Biomarker of Poor Prognosis in Resected Stage I Non-Small-Cell Lung Cancer

Abstract: Background: Although early-stage lung cancer has increased owing to the introduction of screening programs, high recurrence rate remains a critical concern. We aimed to explore biomarkers related to the prognosis of surgically resected non-small-cell lung cancer (NSCLC). Methods: In this retrospective study, we collected medical records of patients with NSCLC and matched tissue microarray blocks from surgical specimens. Semiquantitative immunohistochemistry was performed for measuring the expression level of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…CDCP1, a single-channel transmembrane protein, 4 is overexpressed in NSCLC and is significantly associated with poor prognosis in patients. 5 , 6 , 7 , 8 In malignant tumor cells, CDCP1 can be activated by Src kinase, which promotes the proliferation, invasion, and metastasis of tumor cells through classic signaling pathways such as MAPK (Ras/ERK) and PI3K/AKT. 9 , 10 , 11 , 12 , 13 Besides, numerous studies have demonstrated that antibodies targeting CDCP1, including MAB41-2, MAB10-D7, and C20Fc, can inhibit tumor growth and metastasis in various animal models and improve the efficacy of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDCP1, a single-channel transmembrane protein, 4 is overexpressed in NSCLC and is significantly associated with poor prognosis in patients. 5 , 6 , 7 , 8 In malignant tumor cells, CDCP1 can be activated by Src kinase, which promotes the proliferation, invasion, and metastasis of tumor cells through classic signaling pathways such as MAPK (Ras/ERK) and PI3K/AKT. 9 , 10 , 11 , 12 , 13 Besides, numerous studies have demonstrated that antibodies targeting CDCP1, including MAB41-2, MAB10-D7, and C20Fc, can inhibit tumor growth and metastasis in various animal models and improve the efficacy of chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies on CDCP1 have been carried out mainly by Western blot, confocal microscopy, immunohistochemistry, and other methods to reflect the overall level. 6 , 18 However, the differences of its spatial distribution between cancer cells and normal cells and the relationship between its distribution and function are still unclear. In addition, there are few studies on super-resolution imaging of tissue sections, so the distribution of CDCP1 molecules in tissues has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed FAP-α in NSCLC has been shown in clinical studies to predict NSCLC patients' low survival [6]. Upregulated expression of FAP-α is likely to be correlated with inflammation and suppression of lymphocytedependent immune responses, leading to tumor progression [6,7]. Therefore, targeting FAP might be a potential therapeutic regimen for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Given CDCP1 is highly expressed in RAS-driven cancers, targeting a proteolytic neoepitope on CDCP1 is a pan-cancer approach to control RAS-driven cancers [ 8 ]. In addition, CDCP1 is a prognostic biomarker in early non-small-cell lung cancer, and its high expression predicts a poor prognosis [ 9 ]. Although several studies have preliminarily investigated the oncogenic role of CDCP1 in BrCa [ 10 , 11 ], systematic analysis based on transcriptomics and its prognostic value in BrCa has not been defined yet.…”
Section: Introductionmentioning
confidence: 99%